ADAPTASI TEKNOLOGI BERBASIS CANVA BAGI GURU SEKOLAH DASAR DALAM PROGRAM KAMPUS MENGAJAR BATCH 5 - Ulinnikmah, Fita; Zumrotun, Erna (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
Technology adaptation is the process of changing the way people interact with technology to meet their evolving needs or overcome new challenges. Technological adaptation is used in the world of education to support teacher skills in the teaching and learning process. One of them is in the Class 5 Kampus Mengajar program at SD Negeri 4 Bantrung. This research aims to describe how Canva-based technology is adapted by teachers at SD Negeri 4 Bantrung in the Class 5 Kampus Mengajar program. Data collection techniques in this research include observation, interviews and documentation. Meanwhile, data analysis techniques with steps include data collection, data reduction, data presentation and drawing conclusions. The result of this research is increased teacher creativity in creating learning media using Canva technology. Apart from that, these results have an impact on students' enthusiasm and enthusiasm for learning because the teachers use interesting learning media from the results of Canva-based technology adaptation training